Analysis of Data Obtained From Chromosomal Studies Performed During the Period from 2000-2007 A Retrospective Study - Sadik, Bassam Musa (Journal of the Faculty of Medicine Baghdad, 2008)
Background: Generally, genetic disorders are a leading cause of spontaneous abortion, neonatal death, increased morbidity and mortality in children and adults as well. They a significant health care and psychosocial burden for the patient, the family, the healthcare system and the community as a whole. Chromosomal abnormalities occur much more frequently than is generally appreciated. It is estimated that approximately 1 of 200 newborn infants had some form of chromosomal abnormality. The figure is much higher in fetuses that do not survive to term. It is estimated that in 50% of first trimester abortions, the fetus has a chromosomal abnormality. Aim of the study: This study aims to shed some light on the results of chromosomal studies performed during 7 year-period as these represent a sample of the only registered data available on genetic disorders in Iraq. Patients and Methods: For the period extending from Jan. 1st, 2000 till Jan. 1st, 2007, among all cases referred to the Genetic Clinic, Consultation Clinic, Medical City in Baghdad, Iraq, only those cases indicated for chromosomal study for diagnosis and then genetic counseling were included in this study; they were grouped and then subgrouped accordingly. Results: During the study period, 1720 cases needed chromosomal study for the sake of genetic counseling out of around 5000-8000 cases referred to the clinic during the same period. Mothers having an abnormal child or adverse pregnancy outcome constituted 30.79% of all cases included, followed by the group of children with multiple congenital abnormalities (20.14%), and then cases with primary amenorrhoea (13.97%) and ambiguous genitalia (13.5%). The overall positive findings in the chromosomal studies were 217/1720 (12.61%). Conclusions: Genetic disorders have a great impact on the practice of medicine in all specialties in Iraq. There is a need for a new policy for indications of karyotyping, especially at times of stress.